2015
DOI: 10.1111/cas.12624
|View full text |Cite
|
Sign up to set email alerts
|

New metastatic model of human small‐cell lung cancer by orthotopic transplantation in mice

Abstract: Small-cell lung cancer (SCLC) is an aggressive cancer with high metastatic ability and novel strategies against the metastasis are urgently needed to improve SCLC treatment. However, the mechanism of metastasis of SCLC remains largely to be elucidated. For further studies of SCLC metastasis, we developed a new orthotopic transplantation model in mice. We established a GFP-labeled subline from the human SCLC cell line DMS273 and transplanted them orthotopically into the lung of nude mice with Matrigel. The GFP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Sakamoto et al . showed that treatment with MET inhibitors constrained the formation of distant metastases in SCLC cells showing high HGF production in an orthotopic model . Maulik et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakamoto et al . showed that treatment with MET inhibitors constrained the formation of distant metastases in SCLC cells showing high HGF production in an orthotopic model . Maulik et al .…”
Section: Discussionmentioning
confidence: 99%
“…The human SCLC cell lines SBC‐3 and SBC‐5, were kindly provided by Dr. K. Kiura (Okayama University, Okayama, Japan). DMS237 and DMS273‐G3H were obtained as reported previously . Briefly, DMS273‐G3H was established using tumor cells from a bone metastasis after we had implanted DMS273 orthotopically into the left lung of nude mice.…”
Section: Methodsmentioning
confidence: 99%
“…Human SCLC cell lines NCI‐H69, DMS53, and DMS114 were maintained in RPMI‐1640 medium containing 10% FBS. Human prostate cancer cell line DU‐145, human SCLC cell line DMS273, GFP‐labeled subline DMS273‐GFP, highly metastatic subline G3H, and C5B (S. Sakamoto, H. Inoue & M. Kawada, unpubl. data, manuscript in preparation) were maintained in DMEM (Nissui) containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…injection of the antibodies was started. To prepare the orthotopic transplanted xenograft model of the highly metastatic subline of DMS273 human SCLC cells, 2.5 × 10 5 C5B cells were injected into the left lungs of nude mice as described previously . An Olympus OV110 Small Animal Imaging System (Olympus Corp.) was used for imaging orthotopic and metastatic tumor formation in the orthotopic transplanted xenograft model.…”
Section: Methodsmentioning
confidence: 99%
“…SCLC accounts for ~15% of all new cases of lung cancer, with >150,000 cases every year worldwide 2. Clinically, SCLC is distinguished from NSCLC by aggressive growth and widespread metastasis 3. Most patients with SCLC already show clinically detectable metastases at diagnosis and have extremely poor prognosis even when treated with combined modalities 4.…”
Section: Introductionmentioning
confidence: 99%